Adaptive user assistance in virtual reality shopping - Weiß, Tobias; Justus Liebig University Giessen (My University, 2024)
This dissertation is comprised of five publications in the domain of adaptive user assistance in virtual reality shopping: Weiß, T., Pfeiffer, J. and Pfeiffer, T. (2024). "Early Bird – Predict healthy product choices in virtual commerce". ECIS 2024 Proceedings. 3. Weiß, T. and Pfeiffer, J. (2024). Consumer decisions in virtual commerce: Predict good help-timing based on cognitive load. Journal of Neuroscience, Psychology, and Economics, 17(2), 119. Weiß, T., Merkl, L., & Pfeiffer, J. (2023). Customer decision-making processes revisited: insights from an eye tracking and ECG study using a hidden Markov model. In NeuroIS Retreat (pp. 221-230). Cham: Springer Nature Switzerland. Weiß, T., Eilks, A., Pfeiffer, J., Putze, F., and Schultz, T. (2024). "Real agents in virtual commerce". Working paper. Weiß, T., Pfeiffer, J., and Meißner, M. (2024). "Adaptive product comparison assistance in virtual reality". Working paper.
Keywords: ddc:004; ddc:650